Electrochemical and Morphological Characterization of Zn−Al−Cu Layered Double Hydroxides as a Negative Electrode in Aqueous Zinc‐Ion Batteries. Issue 15 (1st June 2018) - Bani Hashemi, A.; Kasiri, G.; Glenneberg, J.; Langer, F.; Kun, R.; La Mantia, F.
Abstract: Layered double hydroxides (LDH) have shown to improve the zinc electrodeposition efficiency at the negative electrode of aqueous zinc‐ion batteries. In this work, a copper‐doped Zn−Al−CO3 layered double hydroxide (LDH) has been synthesized by co‐precipitation method under constant pH, and investigated as suitable solid‐state additive in zinc‐based negative electrodes. X‐ray diffraction patterns in combination with scanning electron microscope images show that the as‐synthesized LDHs are well crystalline and hexagonal platelet‐like. LDH was mixed with zinc powder in different ratios and the electrochemical performances of the mixtures were characterized by galvanostatic cycling with potential limitation (GCPL) at different current rates. The results show that an appropriate combination of zinc and LDH can be used to reach electrodeposition efficiency equal to 98 %. Thereafter, the performance of this electrode in a full cell is studied. In such configuration, the electrode shows that the electrodeposition efficiency remains high even at high current rates, which is an important characteristic for grid‐scale energy storage. Abstract : An inert kinetic booster : by mixing zinc powder with a layered double hydroxide it is possible to increase the zinc electro‐deposition efficiency from 88 % to 98 % in zinc‐ion batteries. The layered double hydroxide works as a passive substrate for the electro‐deposition process, offering a large surface area with low energy and decreasing the kinetic limitations. This allows reaching more than 250 charging cycles at 98 % efficiency with a C‐rate equal to 5.